Pengaruh Perputaran Kas Dan Perputaran Piutang Terhadap Sisa Hasil Usaha Pada Koperasi Citra Hidup Tribuana Kalabahi Kabupaten Alor - Sau Sabu, Junius Menase (Jurnal Ilmiah Wahana Pendidikan, 2025)
This research aims to examine the influence of cash turnover and accounts receivable turnover on net operating income at Citra Hidup Tribuana Cooperative in Kalabahi, Alor District. This is a quantitative study that employs interview, documentary study, and literature review as data collection techniques. Secondary data was used in this research. The population and sample are the financial statements of Citra Hidup Tribuana Credit Cooperative in Kalabahi, Alor District. Purposive sampling was used as the sampling technique. Multiple linear regression was employed as the statistical method, with the significance value of the t-test and F-test used as benchmarks for hypothesis testing. Data processing was conducted using IBM SPSS 22 for Windows. The results of this study indicate that: (1) Partially, the variable of cash turnover has a significant impact on net operating income, as evidenced by a significance value of 0.016, which is less than the alpha value of 0.05 or 5%. Therefore, the research accepts H1, which states that the variable of cash turnover partially influences the net operating income of Citra Hidup Tribuana Cooperative in Kalabahi, Alor District. (2) Partially, the variable of accounts receivable turnover has a significant impact on net operating income, as evidenced by a significance value of 0.045, which is less than the alpha value of 0.05 or 5%. Therefore, the research accepts H2, which states that the variable of accounts receivable turnover partially influences the net operating income of Citra Hidup Tribuana Cooperative in Kalabahi, Alor District. (3) Simultaneously, the variables of cash turnover and accounts receivable turnover have a significant impact on the net operating income of Citra Hidup Tribuana Cooperative in Kalabahi, Alor District, as evidenced by a significance value of 0.005, which is less than 0.05 or 5%. Therefore, the research accepts H3, which states that the variables of cash turnover and accounts receivable turnover simultaneously influence the net operating income of Citra Hidup Tribuana Cooperative in Kalabahi, Alor District.